High‐level expression of periostin is significantly correlated with tumour angiogenesis and poor prognosis in osteosarcoma - Hu, Fei (Int J Exp Pathol, 2016)
Periostin (PN), originally named as osteoblast‐specific factor‐2 (OSF‐2), has been involved in regulating adhesion and differentiation of osteoblasts. Recently many studies have shown that high‐level expression of PN is correlated significantly with tumour angiogenesis and prognosis in many kinds of human cancer. However, whether and how periostin expression influences prognosis in osteosarcoma remains unknown. This study aimed to examine the expression of PN in patients with osteosarcoma and explore the relationship of PN expression with clinicopathologic factors, tumour angiogenesis and prognosis. Immunohistochemistry was performed to determine the expression of PN in osteosarcoma and osteochondroma respectively. Vascular endothelial growth factor (VEGF) and CD34 were also examined in tissues from the osteosarcoma patients mentioned above. The results showed that PN expression was significantly (P < 0.05) higher in osteosarcoma (80.9%) than in osteochondroma (14.7%). Increased PN protein expression was associated with histological subtype (P = 0.000), Enneking stage (P = 0.027) and tumour size (P = 0.009). The result also showed that high expression of PN correlated with VEGF expression (r = 0.285; P = 0.019) and that tumours with PN‐positive expression significantly had higher microvessal density (44.6 ± 13.7 vs. 20.6 ± 6.5; P = 0.000) compared to those in normal bone tissues. Additionally, the expression of PN was found to be an independent prognostic factor in osteosarcoma patients. In conclusion, our findings suggest that PN may have an important role in tumour progression and may be used as a prognostic biomarker for patients with osteosarcoma.